On Intercultural Interactions - Ghassib, Humam Bishara (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2022)
In this article, physical models and ideas are invoked to describe some overall aspects of intercultural interactions. It is emphasized, however, that actual intercultural interactions are much more complex than any physical or mathematical model can encompass. They constitute, in fact, just one more example of what scientists call complex systems. These ideas are applied to the following examples: (1) Stuart Hall’s The West [versus] the Rest and Samuel Huntington’s weltanschauung; (2) interactions through Science and Technology as well as Science Diplomacy, focusing on Silk-Road interactions. The article is concluded with a partial list of necessary conditions condusive to constructive intercultural interactions, although these cannot possibly be sufficient. The wider implications for Cosmopolitan Education are also underlined.